Evaluative Resources in Medical Research Articles Written by Medical Writers - Swayer, Muna Abdul Hussien; Eesa, Mayada Rahim (Al-Adab Journal, 2019)
Many studies have been presented about the topic of medical researches and articles ,but it has been noticed that the previously mentioned studies haven’t dealt with language usage in terms of attitude and emotional status . Such a topic still needs more attention from scholars and researchers . The current study is expected to enrich the literature about medical articles from a linguistic point of view. The evaluation was done following Martin and White model (2005) which mainly comprised of three important systems ( attitude , engagement and graduation).